Full text in PDF of the EDUCARE journal, issue of February 2014 - EDUCARE, Editor Journal (EDUCARE, 2014)
This journal was firstly published on August 17, 2008. Since issue of February 2009, the EDUCARE-IJES journal has been joining publication between Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto) in Central Java and ASPENSI (Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The EDUCARE journal is published twice a year i.e. every August and February. Starting from issue of August 2013, the EDUCARE-IJES journal has been published by Minda Masagi Press as a publisher owned by ASPENSI in Bandung, West Java, Indonesia.